2022
DOI: 10.3390/land11071038
|View full text |Cite
|
Sign up to set email alerts
|

The Social License to Restore—Perspectives on Community Involvement in Indonesian Peatland Restoration

Abstract: The tropical peatlands of Indonesia are widely recognized as a globally significant carbon stock and an important provider of crucial ecosystem services. However, in recent years they have been increasingly degraded. The Indonesian government has attempted to involve communities in peatland restoration efforts. These attempts were made in recognition of (1) the important role livelihood activities play in land degradation processes and (2) the ‘gatekeeping’ and stewardship role local communities play in ensuri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 69 publications
(127 reference statements)
1
11
0
Order By: Relevance
“…At the five layers, four inputs and nine inputs reach the highest correlation, namely 0.846 for four inputs and 0.886 for nine inputs. (7)(8)(9)(10)(11)(12)(13), and red indicating extreme risk (>13). Overall, the color zones in the upper and lower subplots are similar, except for some discrepancies on 25th and 27th January, where the predicted FWI shifted from green to yellow, and on 6th March, where a blue risk level was predicted as green.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the five layers, four inputs and nine inputs reach the highest correlation, namely 0.846 for four inputs and 0.886 for nine inputs. (7)(8)(9)(10)(11)(12)(13), and red indicating extreme risk (>13). Overall, the color zones in the upper and lower subplots are similar, except for some discrepancies on 25th and 27th January, where the predicted FWI shifted from green to yellow, and on 6th March, where a blue risk level was predicted as green.…”
Section: Resultsmentioning
confidence: 99%
“…Peatland forest fires meet this definition because they can harm the environment, biodiversity, human lives, and property. The rapid spread and intensity of forest fires can lead to the loss of valuable vegetation, the destruction of habitats, the release of greenhouse gases, and the disruption of ecosystem services [7]. Currently, large-scale forest fires have been listed by the United Nations as one of the eight natural disasters in the world [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional income ideally follows Indonesia Law Number 28/2009 regarding local taxation and charging [56]. RA, normatively, brings efficiency, transparency, and accountability in governing people and attracts business; unfortunately, numerous studies have shown that these local regulations are counterproductive in some aspects, including for the agricultural sector and environment [57][58][59], particularly in the forestry sector [60,61].…”
Section: Overview Of Decentralization/regional Autonomy (Ra) and Pres...mentioning
confidence: 99%
“…Efforts employed to exploit peatlands to meet human needs often neglect sustainability. Several studies have identified issues related to peatland mismanagement, including land use, law enforcement, community capacity, economic rentseeking, exploitation of forest products (wood and non-wood), and climate change [1,[4][5][6].…”
Section: Introductionmentioning
confidence: 99%